Rancang Bangun Aplikasi Pengelolaan Kas Berbasis Web Studi Kasus Rt 9 Kanigaran - Dilla Puspita; Dwi Yanto; Ninanesia Rusdiana (Journal Of Informatics And Busisnes, 2025)
Financial management at the neighborhood level (RT) plays a crucial role in supporting transparency and accountability in community administration. However, the recording of transactions is still done manually, resulting in slow processes, a high risk of errors, and inefficiencies in preparing monthly and annual financial reports. Transparency is also limited, as financial information is only accessible through community meetings or direct requests. This study aims to design and develop a web-based cash information system to improve the efficiency, accuracy, and transparency of managing incoming and outgoing funds in RT 09, Kanigaran Subdistrict, Probolinggo City. The research applies the Waterfall system development method, which includes requirement analysis, system design, implementation, testing, and maintenance. The system is tested using the black box testing method to ensure each function operates correctly. The developed application includes key features such as multi-access login, master data management (accounts and residents), recording of income and expenses, and the generation of financial reports accessible based on user roles. The testing results show that the application works effectively, supports the digitalization of financial management at the RT level, and enhances transparency. Thus, this system offers an effective solution for improving financial governance at the neighborhood level.